Métricas de UX aplicadas em realidade virtual: um estudo de caso do Google Arts and Culture - OLIVEIRA, Otávio Henrique Gomes (2019)
Virtual reality is a technology that has conquered its space in up-to-date technological scenery, and it has several applications and possibilities which allows to users to experiment different situations from those ones that such users have lived on day by day. By other hand, the available contents published about user experience (UX) has been focused, in most, on providing several tools that allow to measure such experience. However, authors have not been explored the usage of such tools in virtual reality interfaces. Due to this theoretical gap, the present study aims to offer an outlook on art situation, regarding to both «virtual reality», and «UX metrics» themes, taking into consideration Google Arts & Culture as the object of this study. Thus, it is our purpose to establish possible dialogues among those themes, as weel as to verify the validity of an own method to measure the user experience in virtual reality by means of tests made from of the study object of this search.